VBAC: antenatal predictors of success - Trojano, Giuseppe; Damiani, Gianluca Raffaello; Olivieri, Claudiana; Villa, Mario; Malvasi, Antonio; Alfonso, Raffaello; Loverro, Matteo; Cicinelli, Ettore (Acta Biomedica Atenei Parmensis, 2019)
To determine antenatal factors that may predict successful vaginal birth after Caesarean section (VBAC), to develop a relevant antenatal scoring system and a nomogram for prediction of vaginal birth after caesarean delivery. A non recurring indication for previous Caesarean section (CS), such as breech presentation or foetal distress, is associated with a much higher successful VBAC rate than recurrent indications, such as cephalopelvic disproportion (CPD). Prior vaginal deliveries are excellent prognostic indicators of successful VBAC, especially if the vaginal delivery follows the prior CS. A low vertical uterine incision does not seem to adversely affect VBAC success rates as compared to a low transverse incision. Maternal obesity and diabetes mellitus adversely affect VBAC outcomes. Foetal macrosomia does not appear to be a contraindication to VBAC, as success rates exceeding 50% are achieved and uterine rupture rates are not increased. An inter-pregnancy interval of <24 months is not associated with a decreased success of VBAC. Success rates decrease when interval increases. Twin gestation does not preclude VBAC. Post-dates pregnancies may deliver successfully by VBAC in greater than two-thirds of cases. There are few absolute contraindications to attempted VBAC. Attempted VBAC will be successful in the majority of attempted cases.